MARKET AS MICROECONOMIC ENVIRONMENT - MECHANISMS AND CONTROVERSY - Brkić, Ivana; Stankov, Biljana; Rotarov, Ivana (International Journal of Economic Practice and Policy, 2017)
Contemporary microeconomic principles are based on market ideology. The paper presents the description of market mechanisms, as well as interpreted economic realities in their application. Although none of science stream excludes completely the efficiency and presence of other, it is disputed over the dominance of the market or the state within the economic processes. The gap between two doctrines: market self-regulation vs. state interventionism allows us to highlight the advantages and disadvantages of one and the other concept. The symbiosis of these two institutions - market and state - could give good results in the achievement of social goals, creating a welfare society, and thus deal with the problems of today: the degradation of an environment, the economic crisis and social inequality.